2015
DOI: 10.5935/abc.20150125
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Autonomic Dysfunction in Patients with Morbid Obesity

Abstract: BackgroundMorbid obesity is directly related to deterioration in cardiorespiratory capacity, including changes in cardiovascular autonomic modulation.ObjectiveThis study aimed to assess the cardiovascular autonomic function in morbidly obese individuals.MethodsCross-sectional study, including two groups of participants: Group I, composed by 50 morbidly obese subjects, and Group II, composed by 30 nonobese subjects. The autonomic function was assessed by heart rate variability in the time domain (standard devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
(44 reference statements)
1
9
1
3
Order By: Relevance
“…Studies show that obesity leads to the development of noncommunicable diseases such as hypertension, hypercholesterolemia, insulin resistance, and type 2 diabetes [1][2][3], and also several previous studies have found changes in cardiac autonomic modulation in overweight and obese individuals [4][5][6][7][8], which may be more affected in obese individuals (body mass index (BMI) ≥35.0 kg/m 2 ) [9]. is impairment occurs through an imbalance in the autonomic nervous system (ANS), especially in increased sympathetic modulation and decreased vagal tone leading to decreased heart rate variability (HRV) [5,7,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that obesity leads to the development of noncommunicable diseases such as hypertension, hypercholesterolemia, insulin resistance, and type 2 diabetes [1][2][3], and also several previous studies have found changes in cardiac autonomic modulation in overweight and obese individuals [4][5][6][7][8], which may be more affected in obese individuals (body mass index (BMI) ≥35.0 kg/m 2 ) [9]. is impairment occurs through an imbalance in the autonomic nervous system (ANS), especially in increased sympathetic modulation and decreased vagal tone leading to decreased heart rate variability (HRV) [5,7,10].…”
Section: Introductionmentioning
confidence: 99%
“…is impairment occurs through an imbalance in the autonomic nervous system (ANS), especially in increased sympathetic modulation and decreased vagal tone leading to decreased heart rate variability (HRV) [5,7,10]. e measurement of these patterns can provide a sensitive and early indicator of serious health impairment in obese individuals with a higher risk of multimorbidity and early mortality [9], as they can be indicators of risk of death and cardiovascular disease [2,11,12], such as coronary artery disease, myocardial infarction, sudden death, heart failure and arrhythmias [7,13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, obese pregnant women are more likely to give birth to heavier babies (Carolina, 2014; Sebire, et al., 2001). Obesity has been found to be associated with significantly lower heart rate variability in adult women (Karason, Molgaard, Wikstrand, & Sjostrom, 1999; Rossi, 2015; Sant Anna Junior, 2015). Dragan and Akhtar-Danesh (2007) report that higher body mass index (BMI) may also be associated with more severe forms of depression.…”
mentioning
confidence: 99%
“…Вегетативний профіль у осіб похилого та старечого віку з нормальною вагою тіла характеризується зниженням парасимпатичної активності протягом доби при нормальній симпатичній активності [4]. При цьому в ряді робіт показано зниження активності обох ланок: як симпатичної, так і парасимпатичної нервової системи [6,7]. Розуміння особливостей вегетативної дисфункції при ожирінні має як тера-певтичне, так і профілактичне значення і дозволить проводити ефективну профілактику ускладнень при ожирінні у осіб усіх вікових груп.…”
Section: обґрунтування дослідженняunclassified